Unraveling the genetic potential of native rice (Oryza sativa L.) landraces for tolerance to early-stage submergence - Shanmugam, Aravindan; Manivelan, Kalaiarasan; Deepika, Konne; Nithishkumar, Gopal; Blessy, Viswanadhapalli; Monihasri, Raju Baskaran; Nivetha, Dhanasekar; Roshini, Arunkamaraj; Sathya, Palanivelu; Pushpa, Raman; Manimaran, Rangarajan; Subrahmaniyan, Kasirajan; et al. (Frontiers in Plant Science, 2023)
Direct-seeded rice (DSR) is a promising alternative to the traditional puddled rice system. It has become more popular among rice growers as a result of socioeconomic shifts and global climate change. Although DSR offers advantages, rice plants experience greater anaerobic stress at sowing from unpredicted rainfall. Rice is unique among cereals in its ability to germinate under anaerobiosis. The coleoptile of rice rapidly elongates above the water surface to obtain more oxygen and enhance vigorous seedling growth. A panel of 115 landraces and four check varieties were subjected to anaerobic stress with a water level of 10 cm for up to 15 days. The present study observed significant variation in anaerobic germination percentage (AGP) (10%–100%) and anaerobic vigor index (AVI) (150–4,433). Landraces Karuthakar, Poovan samba, Mattaikar, Edakkal, Manvilayan, and Varappu kudainchan were identified as genotypes tolerant to early water submergence. The shoot and root length of susceptible landraces were significantly lower than the tolerant landraces under hypoxia condition, implying that landraces with longer shoots and roots had a higher survival rate. The response index substantiated this. The results clearly show that tolerant and moderately tolerant landraces possessed higher mean values for root and shoot lengths than susceptible landraces. The landraces grouped under the long–bold category had superior AGP and AVI scores to other grain type groups. This raises the possibility that differences in kernel breadth, which is linked to grain type, could affect anaerobic germination potential. Molecular confirmation using gene-specific markers, viz., DFR, TTP_G4, RM478, RM208, and RM24161, for which the polymorphic information content (PIC) value ranged from 0.36 (RM478) to 0.68 (RM206) suggests that this diverse panel of landraces must be assessed further using advanced molecular tools to precisely clarify the genetic mechanism behind this phenomenon. The tolerant landraces thus identified may become donors in breeding programs. The introduction of these traits would contribute to the development of rice varieties tolerant to anaerobic stress, resulting in sustainable yields. This solution could promote the DSR system across the world.